Latest Clinical Evidence About Effect of Acetylcysteine on Preventing Contrast-Induced Nephropathy in Patients Undergoing Angiography: A Meta-Analysis. (February 2021) - Xie, Wenchao; Liang, Xiangwen; Lin, Zhihai; Liu, Ming; Ling, Zheng
Contrast-induced nephropathy (CIN) is a serious complication of angiographic procedures. It is the third most common cause of hospital acquired acute renal injury. As there are currently no approved therapies for CIN, prevention could be the best strategy to address this issue. Acetylcysteine may indirectly play an antioxidant role by inducing the synthesis of glutathione. Acetylcysteine can also reduce renal vasoconstriction induced by contrast medium stimulation by stabilizing nitric oxide and acting directly or indirectly on renal cortex and medulla microcirculation. To evaluate the effect of acetylcysteine on the prevention of CIN in patients after angiography, we systematically searched and analyzed the clinical data of patients including the incidence of CIN and change in serum creatinine (SCr) at 48 hours after angiography from selected articles. The result showed that acetylcysteine significantly reduces the incidence of CIN (risk ratios: 0.78, 95% CI: 0.68-0.90, I 2 = 37.3%) and the level of SCr (standardized mean difference: −0.53, 95% CI: −0.93 to −0.12, I 2 = 91.5%) after angiography compared with the control group. Overall, the use of acetylcysteine in patients after angiography was associated with a significant reduction of CIN and the level of SCr.